Mental State and Motivation to Physical Exercise in University Students during COVID-19 Pandemic in Poland - Jarosław Muracki; Maria Zadarko-Domaradzka; Emilian Zadarko; Małgorzata Smoter; Ana Filipa Silva; Ewa Kruszyńska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2023)
The Covid-19 pandemic brought consequences for many aspects of people's lives all over the world, such as lockdown, social distancing and reduced accessibility to sports and recreational facilities. The aim of this study was to assess mental state, physical well-being, and motivation to exercise among Polish students of Physical Education and other fields of study, considering their gender, place of living and financial situation. The study involved 1424 students from different universities in Poland. Two questionnaires were used - the EMI-2 to measure motivation to exercise and an original questionnaire to assess daily physical activity, physical and mental well-being. While 31.7% of the students assessed their access to recreational facilities as very poor,71.8% of them rated their financial situation to be average or quite good. Over one-third of the students declared that both their physical and mental well-being (nearly 37% and 33% respectively) were very poor. Among all analyzed motivating factors to exercise, positive health, appearance and strength and endurance were classified as the most important. The importance of different motivating factors differed between the Physical Education students and those of other faculties. To conclude, physical and mental well-being of Polish students during the pandemic was poor. The main reasons were very poor access to recreational facilities, too much time spent in a sitting or lying position daily and insufficient physical activity.